Discrepancies and Similarities in Attitudes, Beliefs, and Familiarity with Vaccination Between Religious Studies and Science Students in Malaysia: A Comparison Study - Elkalmi, Ramadan Mohamed (Journal of religion and health, 2021)
Little is known about the impact of religion on vaccine receptivity in Malaysia. Improved vaccine uptake is positively reflected in the reduction of vaccine-preventable diseases. This study aimed to explore and compare the attitudes, religious beliefs, and familiarity regarding vaccination between the religious studies and science students. A survey-based cross-sectional study was conducted between a convenient sample of students (N = 300) of religious studies and applied sciences in Kuantan, Malaysia. A new, face- and content-validated questionnaire was used for data collection. A total of 206 students responded to the questionnaire, giving a response rate of 86.6%. Overall, participants demonstrated positive attitudes towards vaccination (n = 185, 89.9%). Only a minority of respondents expressed an opposition to vaccination (n = 21, 10.2%). Religious factors (permissibility) of vaccines (n = 12, 57.1%) and harm associated with the vaccine (n = 13, 61.9%) were the most common reasons for not supporting vaccination among the non-supporters. Most (n = 135, 65.5%) respondents agreed that vaccination is parallel with the Islamic concept of protecting life and preventing harm. Almost half of the respondents (n = 98, 47.6%) admit to declaring "Fatwa" to oblige parents to vaccinate their children. Religious beliefs and safety issues surrounding immunisation were reported as the major barriers for the support of immunisation. Well-designed programs are recommended to reshape the religious beliefs and convictions among students toward vaccination.